Pengaruh kepemimpinan transaksional, disiplin kerja, dan motivasi kerja terhadap kinerja pegawai pada BBPJN Jatim-Bali Wilayah III - Firdausi, Fitri; Suroso, Adi; Sedyastuti, Kristina (Universitas Negeri Malang, 2026)
The influence of transactional leadership, work discipline, and work motivation on employee performance at BBPJN East Java–Bali Region III In the context of bureaucratic transformation and increasing demands for public sector accountability, improving employee performance has become a strategic issue, particularly within project-based infrastructure technical organizations. This study aims to analyze the influence of transactional leadership, work discipline, and work motivation on employee performance at the National Road Implementation Agency (BBPJN) East Java–Bali Region III. The study employed a quantitative approach with a causal associative design. Data analysis was conducted using multiple linear regression and bootstrapping techniques to address potential violations of classical assumptions. The study population consisted of 59 permanent employees in the PPK 3.6 units, all of whom were selected as respondents through total sampling. The results indicate that, simultaneously, the independent variables significantly affect employee performance, with F (3,55) = 63.527; p < 0.001; and Adjusted R² = 0.764. Partially, only work motivation has a positive and significant effect, while transactional leadership and work discipline show no significant effect. The novelty of this study lies in testing the transactional leadership model within the context of a government infrastructure project-based technical organization characterized by experienced human resources and a structured work system. The findings reveal that intrinsic motivation is the dominant factor in improving employee performance. The implications of this study emphasize that strengthening work motivation should become a priority in human resource management strategies. In addition, leadership approaches and work discipline policies need to be adjusted to the characteristics of technical organizations to enhance employee performance effectively. Dalam konteks transformasi birokrasi dan tuntutan akuntabilitas sektor publik, peningkatan kinerja aparatur menjadi isu strategis, khususnya pada organisasi teknis berbasis proyek infrastruktur. Penelitian ini bertujuan menganalisis pengaruh kepemimpinan transaksional, disiplin kerja, dan motivasi kerja terhadap kinerja pegawai pada Balai Besar Pelaksana Jalan Nasional (BBPJN) Jatim-Bali Wilayah III. Penelitian menggunakan pendekatan kuantitatif dengan desain asosiatif kausal. Analisis data dilakukan menggunakan regresi linear berganda dan bootstrapping untuk mengatasi potensi pelanggaran asumsi klasik. Populasi penelitian sebanyak 59 pegawai tetap pada unit PPK 3.6 yang seluruhnya dijadikan responden melalui total sampling. Hasil penelitian menunjukkan bahwa secara simultan variabel independen berpengaruh signifikan terhadap kinerja pegawai dengan nilai F(3,55) = 63,527; p < 0,001; dan Adjusted R² = 0,764. Secara parsial, hanya motivasi kerja yang berpengaruh positif dan signifikan, sedangkan kepemimpinan transaksional dan disiplin kerja tidak signifikan. Novelty penelitian ini terletak pada pengujian model kepemimpinan transaksional dalam konteks organisasi teknis berbasis proyek infrastruktur pemerintah dengan karakteristik SDM berpengalaman dan sistem kerja terstruktur. Temuan menunjukkan bahwa motivasi intrinsik merupakan faktor dominan peningkatan kinerja pegawai. Implikasi penelitian ini menegaskan penguatan motivasi kerja menjadi prioritas strategi manajemen SDM. Selain itu, pendekatan kepemimpinan dan disiplin kerja perlu disesuaikan dengan karakteristik organisasi teknis demi efektivitas peningkatan kinerja pegawai.